Post-mortem tenderization of spent layer’s breast meat with calcium chloride (2011)
The effect of calcium chloride (CaCl2) injection at different time post-mortem (PM) on breast meat of spent layer was investigated. Each breast was dissected into two halves with each half weighing between 151.75 and 168.22 g. A total of 36 half breast were randomly assigned to four treatment groups in a completely randomised design. The breast meat were injected with 0.1 M CaCl2 (10% W/W) at 1, 12 and 24 h PM representing Treatments 2, 3 and 4 respectively while treatment one represents non injection at 0 h PM. The injected and non injected samples were aged at 2°C for 24 h. Tenderness was measured with Warner Bratzler shear force machine, drip and cooking losses were determined, proximate composition and eating qualities were also assessed. Injection of samples with CaCl2 improved tenderness by 11.85 to 39.12%. Cooking loss was not affected (P>0.05) by CaCl2 injection while drip loss increased (P<0.05) as time PM injection with CaCl2 increased. Crude protein, moisture and ether extracts were not affected by CaCl2 injection while the ash content of treated samples increased with time PM. The injection of CaCl2 improved the panellist rating (P<0.05) for juiciness, tenderness, ease of fragmentation and overall acceptability however, the flavour score decreased with CaCl2 injection.